Foucault e a (bio) política: possibilidades e metamorfose de um conceito - Góis Filho, Benjamim Julião de (2010)
The fundamental question developed in this research is to consider the possible meanings of biopolitics in the thought of Michel Foucault. In the first chapter of this study seeks to examine the rationality of biopower. It is able to show the rationality of acting as a social machinery for the manufacture of the subjectivity of individuals, biopolitics as a producer of bodies and subjectivity. The theme of biopolitics appears as inspiration of Nietzsche's metaphor of war. The idea that history is the war for dominance of the bodies. In the second chapter, the (bio) political will and political thought of resistance, fighting criticism as an attitude of revolt of the subject before his condition subjugated. The biopolitical here is intended as a conceptual tool for reading the thought / Foucault's work. A resistance that can be thought of as a biopolitical as a "refractoriness reflected". The third chapter will seek to show how the Foucault argues that power was already present the ethics of self-care. If the subject is a product, is captured by the discourse of biopower that manufactures its subjectivity, self care, it's time to think about the inner contents. Self care is something that offers resistance, as a possibility to think that these contents are constructed historically, and that therefore it is possible to reestablish the self-care is a policy of fighting these sedimented content that promotes colonization of the subjects. You can move from ruler to ruled itself, although this pursuit of liberty is always unfinished, always be a tension, a desire for freedom that can be undertaken not as a state, but at least the minimum and temporarily in other forms of existence, and other ways of relating, other ways of sociability, friendship, sexuality